Hydrodynamic instabilities and mix studies on NIF: predictions, observations, and a path forward. (March 2016) - Remington, B. A.; Atherton, L. J.; Benedetti, L. R.; Berzak-Hopkins, L.; Bradley, D. K.; Callahan, D. A.; Casey, D.T.; Celliers, P. M.; Cerjan, C. J.; Clark, D. S.; Dewald, E. L.; Dittrich, T. R.; et al.
Abstract: The goals of the Mix Campaign are to determine how mix affects performance, locate the "mix cliff", locate the source of the mix, and develop mitigation methods that allow performance to be increased. We have used several different drive pulse shapes and capsule designs in the Mix Campaign, to understand sensitivity to drive peak power, level of coast, rise time to peak power, adiabat, and dopant level in the capsule. Ablator material mixing into the hot spot has been shown conclusively with x-ray spectroscopy. The observed neutron yield drops steeply when the hot spot mix mass becomes too large. The mix appears to be driven by ablation- front Rayleigh-Taylor instabilities. A high foot, higher adiabat drive has a more stable ablation front and has allowed the mix mass in the hot spot to be reduced significantly. Two recent high foot shots achieved neutron yields > 10 15 and measured neutron yield over clean 1D simulation (YOC) > 50%, which was one of the central goals of the Mix Campaign.